Using the Book "Al-Miftah lil-‘Ulum" in Teaching Arabic Grammar at the Islamic Boarding School in Indonesia: Benefits and Obstacles: استخدام كتاب المفتاح للعلوم في تعليم قواعد النحو بالمعهد الإسلامي بإندونيسيا: الفوائد والموانع - Hida Zakiya, Fina; Kasih, Baiq Widia Nita; Jamhuri, Wirawan (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
This research aims to comprehend the utilization of the book "Al-Miftah lil-‘Ulum" in teaching Nahwu science at Darul Falah International School, Bagon Mataram, and to identify obstacles arising in teaching Nahwu science using the book. The research methodology employed is qualitative descriptive, utilizing observation, interviews, and documentation as data collection techniques. Data analysis involves data reduction, presentation, and result verification. The findings reveal that the Nahwu science teaching process with the book "Al-Miftah lil-‘Ulum" includes pre-lesson, core activities, and concluding activities. Challenges encountered encompass students' difficulty in reading writings on the board, specific difficulties in each volume, student boredom, and teacher absenteeism hindering goal achievement. Teacher obstacles include student delays, students not bringing books during teaching, non-repetition of "Al-Miftah lil-‘Ulum" lessons in the dormitory, difficulty understanding students' abilities, classroom management challenges, and difficulty providing motivation. This research supports recommendations to explore the effectiveness of "Al-Miftah lil-‘Ulum" as a Nahwu learning source and evaluate its teaching methods. It is suggested to focus on its impact on students' understanding and strategies to enhance its integration into the official curriculum. The research encourages exploring student responses to the book's use, identifying challenges, and proposing solutions through qualitative and quantitative methods for comprehensive understanding.